Surface-Treated versus Untreated Large-Bore Catheters as Vascular Access in Hemodialysis and Apheresis Treatments - Rolf Bambauer; Ralf Schiel; Carolin Bambauer; Reinhard Latza (International Journal of Nephrology)
Background. Catheter-related infections, thrombosis, and stenosis are among the most frequent complications associated with catheters, which are inserted in vessels. Surface treatment processes of the outer surface, such as ion-beam-assisted deposition, can be used to mitigate such complications. Methods. This retrospective study (1992–2007) evaluated silver-coated (54 patients) and noncoated (105 patients) implanted large-bore catheters used for extracorporeal detoxification. The catheters were inserted into the internal jugular or subclavian veins. After removal, the catheters were cultured for bacterial colonization using standard microbiologic assays. They also were examined using scanning electron microscope. Results. The silver coated catheters showed a tendency towards longer in situ time. The microbiologic examinations of the catheter tips were in both catheter types high positive, but not significant. Conclusion. The silver-coated catheters showed no significantly reduction in infection rate by evaluation of all collected data in this retrospective study. There was no association between both catheters in significantly reducing savings in treatment costs and in reducing patient discomfort. Other new developed catheter materials such as the microdomain-structured inner and outer surface are considered more biocompatible because they mimic the structure of natural biological surface.